Synthesis of the Kallman's filter of the second order at observation of radial range and speed - S. A. Gorshkov; V. N. Zavizhenets (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The features of the radial speed application in the problem of Kallman's filtration of range and two its derivatives for the surveillance radar are considered. The comparative analysis of the consielired parameters of the filtration results for the hypothetical radars is performed. The total fluctation and dynamic errors are analysed.